Interscale and Interlevel Problems of Research on Social Capital in Rural Japan - Kenji Tsusumi (European Regional Science Association (ERSA), 2010)
In Japan, most of the studies of 'Social Capital' (SC) are from a viewpoint of macro scale such as national, and also mainly by a top-down way. Therefore, the accumulation of studies in micro scale?(bottom-up way), such as a village or a community, is an urgent and vital task for researchers. Diversity of the scale of study is very important, but such approach lacks and is weak there in fact. On the one hand, many studies of SC are from a macro viewpoint mentioned as above, and on the other hand, researches of social ties in modern and contemporary Japanese rural sociology and rural studies had shown huge amounts of research results on rural villages from a micro view. But since the high economic growth in this country we have been seen urbanization, depopulation, or rapid aging in Japanese rural villages, and they have been diversified, so the framework of simplified rural-urban dichotomy became old-fashioned to analyze them. Especially in disadvantaged rural depopulated regions, however, we need revision of social ties or SC in order to sustain functions for daily life. On the basis of such situation, the author examines important elements on considering SC with some regional examples of positivistic study. In a region, SC consists of social ties and their networks. The forms of combination of the ties are varied, often crossing over several kinds of scales and levels. Actually in such a structure of something complex, complicated network or 'Social Scape' is formed, with 'bonding' and 'bridging' being connected each other complicatedly.
Keywords: 330; social capital; inter-scale; inter-level; rural Japan